PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI MASKER KAIN DI SAVEME BANDUNG - Sri Septia Mulyani; Prihartono Prihartono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research aimed to find out how much influence the quality of the product has on the interest in buying cloth masks in Saveme Bandung. Using a quantitative approach, survey methods were selected for use in the study. As a data collection tool, the dissemination of questionnaires that have been compiled based on eight dimensions of product quality and four indicators of buying interest. In this study, the population used was a customer who bought cloth mask products at Saveme Bandung in December 2021, and got as many as 41 populations calculated using the slovin formula to find out how many samples can be taken. The results of the questionnaire are then carried out various tests such as, validity and reliability tests, heteroskedasticity tests, normality tests, coefficients of determination, so that they contain the required data and processed using the application of statistical analysis program, namely SPSS. In addition, the t test (partial test) and a simple linear regression test showed the positive effect of variable X on Y. Then it can be known that the quality of cloth masks in Saveme Bandung is influenced by the quality of the product up to 56%. The remaining 44% is affected by variables other than this regression or untested variables.